2010
DOI: 10.1088/0964-1726/19/6/065004
|View full text |Cite
|
Sign up to set email alerts
|

GA-based optimum design of a shape memory alloy device for seismic response mitigation

Abstract: Damping systems discussed in this work are optimized so that a three-story steel frame structure and its SMA bracing system minimize response metrics due to a customtailored earthquake excitation. Multiple-objective numerical optimization that simultaneously minimizes displacements and accelerations of the structure is carried out with a genetic algorithm (GA) in order to optimize SMA bracing elements within the structure. After design of an optimal SMA damping system is complete, full-scale experimental shake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…SMA‐based dampers have been employed for seismic vibration control of cable‐stayed bridges . Parametric studies have also been conducted to propose a range of optimal parameters in such system. The optimal range of design variables is also suggested for the SMA‐based seismic isolation by Ozbulut and his co‐workers by adopting a framework based on genetic algorithm .…”
Section: Introductionmentioning
confidence: 99%
“…SMA‐based dampers have been employed for seismic vibration control of cable‐stayed bridges . Parametric studies have also been conducted to propose a range of optimal parameters in such system. The optimal range of design variables is also suggested for the SMA‐based seismic isolation by Ozbulut and his co‐workers by adopting a framework based on genetic algorithm .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recently developed hybrid optimization methodology, combining the local and global search algorithms, has proved to be a useful tool in studying the dynamics of phase combinations in SMA samples [74]. A similar idea based on the genetic algorithm was recently pursuit in [75] specifically in the context of damping systems and seismic response mitigation.…”
Section: Dynamic Models and Their Approximationsmentioning
confidence: 99%
“…It demonstrated that the BRB component provided energy dissipation and the SMA rods provided the self‐centering and additional energy dissipation. Ozbulut et al investigated the performance of super‐elastic Ni–Ti SMAs for the seismic applications through numerical and large‐scale experiment. SMA damping devices were installed to a steel frame structure, and the residual displacements of the SMA‐braced frame were significantly reduced after the excitation was moved.…”
Section: Introductionmentioning
confidence: 99%